Eventos adversos na utilização do cateter venoso central de inserção periférica em um hospital público infantil - Sá, Jaciane Soares de (2013)
The Catheter Peripherally Inserted Central is a device used in intravenous therapy in neonatal intensive care units and pediatric and in neonatal intermediate care units, which promotes venous access safe for a long time and with a low rate of infection, however, the use of this technology by being a complex process, may be subject to adverse events. The aim of the study was to analyze the use of central venous catheter peripherally inserted into a child public hospital from the perspective of nurses, identify and classify the events in the stages of the process of insertion, maintenance and removal of PICC and verify the procedures adopted in these events and the consequences for patients. Descriptive analysis was performed of the results, with minimum and maximum for continuous variables and absolute and relative frequencies for categorical variables. Qualitative data were grouped and categorized by approaching answers. Results The results showed a predominance of females with an average age between 24-58 years and 5 or more years of professional performance, function and institution. The working day was 30 hours per week and 53.8% were specialists with training course for handling PICC. 84.6% witnessed some kind of adverse event, 57.7% in the insertion, highlighting the difficulty of progression / closing valve / capillary fragility; 84.6% in keeping with an obstruction of the catheter 61.5% EA as mentioned, caused by the blood reflux, drug incompatibility, poor permeabilization and lack of washing (flushing) of the catheter; and 15.4% in recession, caused by rupture / breakage of the catheter. The adopted clinical management were the exchange of venous access, monitoring, traction of the catheter and pressure dressing in case of bleeding. The consequences for patients were prolonged length of stay in the service, need to complement therapy and new IV line installation. The results signaled the size of adverse event occurrences in the safe use of PICC, the safety measures and quality of patient care, requiring the training of nursing professionals, combined with a policy of promoting continuing education activities and formulation strategies to minimize flaws and building a professional and institutional culture of safety.